(untitled) (Research, Society and Development, 2023)
The objective of this research was to characterize users with hypertension and/or diabetes in a Family Health Unit in the city of Mossoró - RN and to identify possible associations between risk factors and comorbidities. This is a cross-sectional, descriptive and quantitative research, through interviews with a semi-structured element. There was a high prevalence of females, aged over 60 years, schooling between 4 and 8 years, married, retired and with family history. Of the participants, 15 (14%) were registered as having Diabetes Mellitus, 36 (35%) with Systemic Arterial Hypertension and 53 (51%) with both associated comorbidities. Statistical significance was observed between comorbidities and risk factors such as smoking, alcohol consumption, waist circumference at high risk and overweight/obesity. The importance of continuing to include prevention and health promotion actions related to chronic non-communicable diseases such as Systemic Arterial Hypertension and Diabetes Mellitus was highlighted.